2007
DOI: 10.1002/mrc.2054
|View full text |Cite
|
Sign up to set email alerts
|

A predictive tool for assessing 13C NMR chemical shifts of flavonoids

Abstract: Herein are presented the (1)H and (13)C NMR data for seven monohydroxyflavones (3-, 5-, 6-, 7-, 2'-, 3'-, and 4'-hydroxyflavone), five dihydroxyflavones (3,2'-, 3,3'-, 3,4'-, 3,6-, 2',3'-dihydroxyflavone), a trihydroxyflavone (apigenin; 5,7,4'-trihydroxyflavone), a tetrahydroxyflavone (luteolin; 5,7,3',4'-tetrahydroxyflavone), and three glycosylated hydroxyflavones (orientin; luteolin-6C-beta-D-glucoside, homoorientin; luteolin-8C-beta-D-glucoside, vitexin; apigenin-8C-beta-D-glucoside). When these NMR spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 42 publications
1
28
0
3
Order By: Relevance
“…The 13 C chemical shifts reported by Ares et al [5] have been assigned on a matching basis Recently, Park et al [6] published the 1 H NMR and 13 C chemical shifts for flavone and 19 substituted flavones among which was 7,8,4 -trihydroxyflavone; the solvent was dimethylsulphoxide-d 6 . The predictive tool of Burns et al [4] can be operated in reverse to obtain the 13 C chemical shifts for 8-hydroxyflavone using the measured values of 13 C chemical shifts for 7,8,4 -trihydroxyflavone, 7-hydroxyflavone, and 4 -hydroxyflavone. This procedure was accomplished in the following manner:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C chemical shifts reported by Ares et al [5] have been assigned on a matching basis Recently, Park et al [6] published the 1 H NMR and 13 C chemical shifts for flavone and 19 substituted flavones among which was 7,8,4 -trihydroxyflavone; the solvent was dimethylsulphoxide-d 6 . The predictive tool of Burns et al [4] can be operated in reverse to obtain the 13 C chemical shifts for 8-hydroxyflavone using the measured values of 13 C chemical shifts for 7,8,4 -trihydroxyflavone, 7-hydroxyflavone, and 4 -hydroxyflavone. This procedure was accomplished in the following manner:…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this work, a predictive tool was developed for assessing 13 C NMR chemical shifts of flavonoids. [4] This simple tool is based upon the cumulative differences between the 13 C chemical shifts for carbon atoms in monohydroxyflavones and those for the corresponding carbon atoms in flavone. The purpose of this tool is to predict rapidly 13 C NMR spectra of flavonoids and to assign substitution patterns in newly isolated flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…The substitution of formic acid aqueous solution 0.5% (v/v) as eluent (A) for TFA solution affected the retention times of both peaks and they elluted before 30 min. The gradient profile of the organic modifier MeOH (B) was, thus, adjusted in order to trap orientin (1, t R = 27.0 min, 600 µg), 31,32 and isoorientin (2, t R = 29.0 min, 500 µg) 31,32 flavonoids. For the second section of the original chromatographic profile with compounds that eluted after 50 minutes, 26 the exchange of methanol as the modifier for acetonitrile led to higher resolution which improved the trapping process.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 To further furnish insight in the chemical structures of compounds 1 and 2 they were also submitted to analysis by (-)ESI-ITMS 2 (electrospray ionization-ion trap tandem mass spectrometry). -, which are representative of 0,3 X and 0,2 X glucose cross-ring cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…The sugar moiety was identified by a careful analysis of vicinal coupling patterns as b-glucopyranose, with a J(1'',2'') value of 10.1 Hz confirming b-linkage. The chemical shift of C(1'') (d(C) 74.5) was indicative of a C-glycosidic linkage [4] [12]. Analysis of 1 H-NMR spectra confirmed that ring A was fully substituted (Table).…”
mentioning
confidence: 80%